Pengaruh Pengetahuan dan Pemahaman, Efektifitas Sistem Perpajakan, dan Pelayanan Fiskus Terhadap Kemauan Membayar Pajak Dengan Kesadaran Membayar Pajak Sebagai Variabel Intervening. (Studi Empiris pada KPP Pratama Bangkinang) - Daud Indrawan; Azwir Nasir; Volta Diyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the effect of knowledge and understanding, effectiveness of the system of taxation and service tax authorities on the willingness to pay taxes and the role of consciousness pay taxes as an intervening variable. Model variables tested is knowledge and understanding, the effectiveness of the tax system, the quality of service tax authorities, the willingness to pay taxes and pay taxes consciousness.The population in this study is Bangkinang STO. This study used a sample of 74 respondents. The type of data used is primary data by using questionnaire method of data collection. Data analysis method used is multiple regression with SPSS statistical software version 20.00. The results showed that the variables of knowledge and understanding, effectiveness of the system of taxation and service tax authorities have a significant effect on the consciousness of paying taxes. Similarly, the awareness of the tax paying significant effect on willingness to pay taxes.Keywords: knowledge and understanding, effectiveness sisitem taxation, service tax authorities, pay taxes awareness, willingness to pay taxes.